Potential of agricultural residues from Musa acuminata (Cavendish) peel: study on physicochemical properties and thin-layer drying characteristic - Nur Arnisah, Ishak; Mohd Sabri, Pak Dek; Azhari, Samsu Baharuddin; Nor Asma, Razak Abd (College of Graduate Studies, Walailak University, 2023)
Musa acuminata (Cavendish) peel is a waste product of limited values that is generated in large quantities and caused detrimental environmental issues in long term if there are no alternative solutions. This primary residue corresponds to 40 % of the fruit weight with a broad natural antioxidant such as polyphenols that will be valuable to the food industry application. This study aimed to investigate the physicochemical characteristics and solvent extraction for high polyphenols recovery between unripe and ripe peel following the drying characteristic and quantification analysis. The physicochemical characteristics of Cavendish peel showed significant differences at different ripening stages, thus effect the solvent extraction towards antioxidant compounds and activities. An aqueous extract of unripe peel was the best solvent for higher phenolic, tannin and flavonoid content compared to ripe peel. The 40 °C of drying treatment will preserve higher tannin content than other temperature and eleven profile of polyphenols had been detected using HPLC including tannic acid as a lead compound. The results from this study can be used for further isolation and purification of tannin to the possible application as functional food ingredients due to its antioxidants benefits and conversion of this residues as valuable is necessary.